Knowledge on hypothyroidism and associated factors on it among hypothyroidism patients attending endocrinology clinic at Teaching hospital Jaffna - Gowthamy, K.; Kobinath, V.; Jegapragash, V.; Aravinthan, M. (University of Jaffna, 2023)
Introduction: Hypothyroidism is a relatively second most common endocrine disorder and if it is not treated properly, it can lead to complications. Adequate knowledge about disease and treatment is important to improve quality of life and prevent the progress of disease affecting health. Objective: To assess the Knowledge on hypothyroidism and associated factors on it among hypothyroidism patients attending Endocrinology Clinic at Teaching Hospital, Jaffna. Methodology: This was a hospital based descriptive cross-sectional study among 278 Hypothyroidism patients in the Endocrinology Clinic at Teaching Hospital Jaffna. Pre-tested and validated interviewer-administered questionnaire was used to collect the data. The data were analysed by using IBM SPSS Statistics 25. The variables were described by using mean, standard deviation, percentages, and frequencies. The Chi-Squared test was used to find the association between knowledge and the factors. The ethical clearance was obtained from Ethics Review Committee of Faculty of Medicine, University of Jaffna. Results: The mean age of the participants was 35 years (SD=14.289). The majority of the participants were females (89.6%). More than half of participants studied up to O/L (51.8%) and two third of them (66.5%) were married. Three fourth of the participants (75.2%) had adequate knowledge on hypothyroidism. More than three quarter of participants (76.6%) knew that women had a high risk to develop hypothyroidism. There were significant associations found between knowledge and socio-demographic variables such as age (p=0.001), gender (p=0.002), educational level (p=0.002), and marital status (p=0.041). Conclusion: the findings revealed that most of the participants had adequate knowledge on hypothyroidism. It is recommended to educate other participants also for getting optimal care.
Keywords: Hypothyroidism; Knowledge; Jaffna